1987
DOI: 10.1136/jcp.40.5.486
|View full text |Cite
|
Sign up to set email alerts
|

Cell surface expression of beta 2-microglobulin (beta 2m) correlates with stages of differentiation in B cell tumours.

Abstract: SUMMARY Cell surface 32-microglobulin (f2m) densities of malignant B cells were determined by enzyme immunoassay in 97 cases of immunologically defined lymphoproliferative disease. Absolute f2m densities were found to depend on disease category with the lowest levels found on cells from chronic lymphocytic leukaemia (mean = 5-6 ng/106 cells, n = 27); atypical chronic lymphocytic leukaemia (mean = 5.9 ng/106 cells, n = 8); and prolymphocytoid chronic lymphocytic leukaemia variant (mean = 6 0 ng/106 cells, n = 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1987
1987
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 27 publications
(2 reference statements)
0
2
0
Order By: Relevance
“…This indicates the independence of immunoglobulin and (32m synthesis in spite of their homology, which corresponds to in vitro experiments [24], The origin of increasing (32m production in malignant disease progression has not been established, but it was specu lated that the rise in serum (32m seen in the progression of some B-cell tumors to more clinically aggressive forms may be accom panied by a reduction in surface p2m expression [25], Higher p2m levels in IgD and light-chain myeloma could be re lated to their general poor prognosis. These patients often de velop renal complications because of Bence-Jones proteinuria.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates the independence of immunoglobulin and (32m synthesis in spite of their homology, which corresponds to in vitro experiments [24], The origin of increasing (32m production in malignant disease progression has not been established, but it was specu lated that the rise in serum (32m seen in the progression of some B-cell tumors to more clinically aggressive forms may be accom panied by a reduction in surface p2m expression [25], Higher p2m levels in IgD and light-chain myeloma could be re lated to their general poor prognosis. These patients often de velop renal complications because of Bence-Jones proteinuria.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that cell surface expression of P2m shows broadly considerable variation in patients with nonHodgkin's lymphomas, presumably reflecting the heterogeneity of these disorders (Jones et al, 1987). Of all the biochemical indicators investigated in the lymphomas, serum lactic dehydrogenase (LDH) has enjoyed the most universal acceptance.…”
Section: Biochemical Markersmentioning
confidence: 99%